THE PEDAGOGICAL PRACTICES OF A TEACHER OF PORTUGUESE FOREIGN LANGUAGE (PLE) IN IMMERSION AND NON-IMMERSION CONTEXT - Rocha, Nildiceia Aparecida [UNESP]; Silveira Gileno, Rosangela Sanches da [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2016)
The aim of this paper is to present a reflection on the specifics of teaching Portuguese as a Foreign Language (PLE) both in the context of immersion and outside it, from the observations carried out in two stages: first, the practice of a teacher PLE will be described in immersion situation at a university in the state of Sao Paulo, Brazil; and then practice the same teacher in a course of PLE out of the immersion context, at a university in Spain, in a provincial capital. In this sense, the teaching practice will be analyzed from a teacher of PLE in immersion situation and beyond when the didactic and pedagogical treatment of the inseparable relationship between language and culture within an intercultural communicative approach. It is a qualitative research in which it is a case of state, showing the practice of one teacher (research subjects) in two socio-historically different contexts, but with the same approach. The survey results indicate that the teacher's practice in non -immersion context had to be re-signified to enable PLE learning in such a context. In fact, the teacher had to redefine their practice and deconstruct a belief and turn to the theory, according to their didactic and pedagogical and linguistic concerns, finding that the examination of social, historical and cultural data should always be the guiding and / or determinants as regards the teaching of a foreign language, in particular PLE out of immersion.
Keywords: Teaching Practice; Portuguese Foreign Language Teaching; Immersion Context; Language And Culture